PvdP Is a Tyrosinase That Drives Maturation of the Pyoverdine Chromophore in Pseudomonas aeruginosa - Nadal-Jimenez, Pol (American Society for Microbiology, 2014)
The iron binding siderophore pyoverdine constitutes a major adaptive factor contributing to both virulence and survival in fluorescent pseudomonads. For decades, pyoverdine production has allowed the identification and classification of fluorescent and nonfluorescent pseudomonads. Here, we demonstrate that PvdP, a periplasmic enzyme of previously unknown function, is a tyrosinase required for the maturation of the pyoverdine chromophore in Pseudomonas aeruginosa. PvdP converts the nonfluorescent ferribactin, containing two iron binding groups, into a fluorescent pyoverdine, forming a strong hexadentate complex with ferrous iron, by three consecutive oxidation steps. PvdP represents the first characterized member of a small family of tyrosinases present in fluorescent pseudomonads that are required for siderophore maturation and are capable of acting on large peptidic substrates.